Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To prove [tex]\(\cos^2(\theta) + \sin^2(\theta) = 1\)[/tex] from the given equation [tex]\(x^2 + y^2 = r^2\)[/tex], follow these steps:
1. Statements: [tex]\(x^2 + y^2 = r^2\)[/tex]
Reasons: Given
2. Statements: [tex]\(\frac{x^2}{r^2} + \frac{y^2}{r^2} = \frac{r^2}{r^2}\)[/tex]
Reasons: Divide each term by [tex]\(r^2\)[/tex]
3. Statements: [tex]\(\left(\frac{x}{r}\right)^2 + \left(\frac{y}{r}\right)^2 = 1\)[/tex]
Reasons: Simplified
Continuing from the simplified equation:
- We know from trigonometry that:
[tex]\(x = r \cos(\theta)\)[/tex] and [tex]\(y = r \sin(\theta)\)[/tex]
- Substituting these values into the equation:
[tex]\[ \left(\frac{r \cos(\theta)}{r}\right)^2 + \left(\frac{r \sin(\theta)}{r}\right)^2 = 1 \][/tex]
- This further simplifies to:
[tex]\[ \cos^2(\theta) + \sin^2(\theta) = 1 \][/tex]
Thus, we have proven that [tex]\(\cos^2(\theta) + \sin^2(\theta) = 1\)[/tex].
[tex]\[ \begin{array}{|l|l|} \hline \text{Statements} & \text{Reasons} \\ \hline 1. x^2 + y^2 = r^2 & \text{1. Given} \\ \hline 2. \frac{x^2}{r^2} + \frac{y^2}{r^2} = \frac{r^2}{r^2} & \text{2. Divide each term by } r^2 \\ \hline 3. \left(\frac{x}{r}\right)^2 + \left(\frac{y}{r}\right)^2 = 1 & \text{3. Simplified} \\ \hline \end{array} \][/tex]
1. Statements: [tex]\(x^2 + y^2 = r^2\)[/tex]
Reasons: Given
2. Statements: [tex]\(\frac{x^2}{r^2} + \frac{y^2}{r^2} = \frac{r^2}{r^2}\)[/tex]
Reasons: Divide each term by [tex]\(r^2\)[/tex]
3. Statements: [tex]\(\left(\frac{x}{r}\right)^2 + \left(\frac{y}{r}\right)^2 = 1\)[/tex]
Reasons: Simplified
Continuing from the simplified equation:
- We know from trigonometry that:
[tex]\(x = r \cos(\theta)\)[/tex] and [tex]\(y = r \sin(\theta)\)[/tex]
- Substituting these values into the equation:
[tex]\[ \left(\frac{r \cos(\theta)}{r}\right)^2 + \left(\frac{r \sin(\theta)}{r}\right)^2 = 1 \][/tex]
- This further simplifies to:
[tex]\[ \cos^2(\theta) + \sin^2(\theta) = 1 \][/tex]
Thus, we have proven that [tex]\(\cos^2(\theta) + \sin^2(\theta) = 1\)[/tex].
[tex]\[ \begin{array}{|l|l|} \hline \text{Statements} & \text{Reasons} \\ \hline 1. x^2 + y^2 = r^2 & \text{1. Given} \\ \hline 2. \frac{x^2}{r^2} + \frac{y^2}{r^2} = \frac{r^2}{r^2} & \text{2. Divide each term by } r^2 \\ \hline 3. \left(\frac{x}{r}\right)^2 + \left(\frac{y}{r}\right)^2 = 1 & \text{3. Simplified} \\ \hline \end{array} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.